The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s10763-016-9770-6
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Assessing Reading Comprehension of Geometric Construction Texts

Abstract: This study investigates one issue related to reading mathematical texts by presenting a two-dimensional framework for assessing reading comprehension of geometric construction texts. The two dimensions of the framework were formulated by modifying categories of reading literacy and drawing on key elements of geometric construction texts. Three categories of reading mathematical texts were recognized and then cross-tabulated with three key elements of geometric construction texts to create a nine-category asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
0
6
0
10
Order By: Relevance
“…Many researchers have even suggested that learning through reading can be improved (Sabatini, Albro and O'Reilly, 2012). However, it is stated that existing studies are insufficient in evaluating how texts are read by students and a framework is needed to evaluate how students read it to understand a structure text (Yang and Lin, 2018). In this context, Yang and Lin (2018) developed a framework of building texts that revealed the knowledge that students had in order to distinguish between shapes and figures, geometric relations and spatial realities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have even suggested that learning through reading can be improved (Sabatini, Albro and O'Reilly, 2012). However, it is stated that existing studies are insufficient in evaluating how texts are read by students and a framework is needed to evaluate how students read it to understand a structure text (Yang and Lin, 2018). In this context, Yang and Lin (2018) developed a framework of building texts that revealed the knowledge that students had in order to distinguish between shapes and figures, geometric relations and spatial realities.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is stated that existing studies are insufficient in evaluating how texts are read by students and a framework is needed to evaluate how students read it to understand a structure text (Yang and Lin, 2018). In this context, Yang and Lin (2018) developed a framework of building texts that revealed the knowledge that students had in order to distinguish between shapes and figures, geometric relations and spatial realities. In this study, it is aimed to evaluate how the students make a reading in order to understand the geometric texts that explain the formation process of the square which is frequently encountered in primary, secondary and high school life.…”
Section: Discussionmentioning
confidence: 99%
“…Debido a la perspectiva del área matemática en estudio, la cual concuerda con la OCDE (2017), MEP (2012) y Yang & Li (2018), los autores incluyen en sus instrumentos aspectos vinculados con la capacidad de describir, usar y visualizar los efectos de componer y descomponer formas geométricas.…”
Section: Evaluación En Educación Matemática Y Metodologíaunclassified
“…De acuerdo con Yang & Li (2018) es necesario evaluar la comprensión de lectura, en particular si se le considera como medio de aprendizaje. Además, señalan que ser un buen lector, no garantiza ser buen lector de textos matemáticos.…”
Section: Comprensión Lectora Y Construcción Geométricaunclassified
See 1 more Smart Citation